Composición numérica en Petrarca, Boscán y Shakespeare. Nota sobre el caso de Sir Thomas Wyatt y Garcilaso de la Vega - Armisén, Antonio (Cuadernos de Filología Italiana, 2005)
Although the number of Shakespeare’s Sonnets, 154, is possibly related to the figure 153 of the miraculous fishing in the Gospel (John, XXI, 1-14), as was pointed out by A. Fowler (1970), T.P. Roche (1989) and is mentioned in K. Duncan-Jones edition (1997), precedents in the use of this figure in can - zonieri by Continental Petrarchists and in other genres are ignored by students of early modern English poetry. This paper continues previous work on elements of the numerological exegesis of Augustine of Hippo (In Iohann. evang. tract., 122) in Juan Boscán’s Libro II (1543) – the first canzoniere to be printed in Spanish- and in Petrarch’s Canzoniere as a precedent. The paper calls for a revaluation of the influence of Spanish Petrarchism on English poetry in this period, and advances some proposals which will be futher substantiated in the forthcoming book Composición numérica, petrarquismo y redención («Numerological Composition, Petrarchism and Redemption»). The paper ends with a brief interpretation of an ottava rima by Thomas Wyatt, written on his leaving Spain in 1939, which is considered here a veiled homage to Garcilaso de la Vega.